Protective effect of MP-40 mitigates BDL-induced hepatic fibrosis by inhibiting the NLRP3-mediated pyroptosis - Wan, Xuedong; Fang, Yuanyuan; Qin, Minjing; Zheng, Qitong; Yang, Qiao; Peng, Mengyun; Hao, Min; Wang, Kuilong; Zhao, Ruihua; Shi, Yiqing; Han, Xin; Sang, Xia’nan; et al. (Frontiers in Pharmacology, 2024)
Background: Hepatic fibrosis and its associated consequences continue to pose a substantial global health challenge. Developing novel approaches to hepatic fibrosis management and prevention is critically necessary. Radix Paeoniae Alba (RPA) is widely used in Traditional Chinese Medicine (TCM) to treat various diseases. Our earlier research found that a bioactive component of RPA had a dose-dependent effect on anti-allergic asthma. RPA reduces allergic asthma by slowing the hepatic wind, according to "Treatise on Febrile Diseases". However, this bioactive fraction's pharmacological effects and mechanisms on the liver are unknown. Aim: This study examined the bioactive fraction MP-40, the methanol extract of RPA (MRPA), on bile duct ligation (BDL) for its anti-hepatic fibrosis activity and potential mechanisms. Methods: First, the effectiveness of MP-40 in treating BDLinduced hepatic fibrosis in mice and rats was evaluated through survival rates, ALT, AST HYP, and pathological changes. Molecular assays were performed using in vitro cultures of HSC-T6 activation. The expression of α-SMA and Collagen I evaluated fibro-tropic factors with HSC activation. Furthermore, the levels of pyroptosis were assessed by examining the expression of the pyroptosisrelated proteins, including NLRP3, Cleaved Caspase-1, GSDMD-N, and 1L-1β. Additionally, the effective constituents of MP-40 were identified by extraction, separation, and identification. Finally, PF and TGG, as the delegate compounds of MP-40, were tested to confirm their inhibition effects on HSC-T6 activation. Results: The findings demonstrated that MP-40 and MRPA could lower ALT, AST, and HYP levels, boost survival rates, and reduce liver damage in BDL mice and rats. Furthermore, MP-40 outperforms MRPA. MP-40 was proven to drastically diminish fibrotic α-SMA and Collagen I. The expression of pyroptosis-related proteins NLRP3, Cleaved Caspase-1, TGF-β1, GSDMD-N, and 1L-1β decreased. MP-40 inhibited the synthesis of pyroptosis-related proteins more effectively than MCC950 (an NLRP3-specific inhibitor). Monoterpene glycosides and tannins were shown to be the most potent MP-40 components. Finally, the delegate compounds MP-40, PF, and TGG were shown to have substantial inhibitory effects on HSC-T6 activation. Conclusion: The results proved that MP-40 alleviates BDL-induced cholestatic hepatic fibrosis by inhibiting NLRP3-mediated pyroptosis. PF and TGG play a role in treating BDL-induced cholestatic hepatic fibrosis in MP-40.